ANALISIS KELAYAKAN USAHA SAPI PERAH (STUDI LAPANG DI PETERNAKAN BAPAK KHOIRI DESA GLEDUG KECAMATAN SANANKULON KABUPATEN BLITAR) - Shela Asperinche; Agustina Widyasworo; Nita opi ari kustanti (Universitas Islam Balitar, 2020)
The research was carried out at Mr. Khoiri’s farm in Gledug Village, Sanankulon District, Blitar Regency. This study aims to determine the feasibility of the dairy cattle business in Mr. Khoiri’s farm, Gledug Village, Sanankulon District, Blitar Regency. This research material used 30 cows owned by Mr. Khoiri. The method used in this research is a field study, by collecting data, interviewing with a list of questions and observations (observations). The feasibility of Mr. Khoiri’s dairy farming business for three years obtained an B/C value of 0,64 and R/C 1,6. NPV value of Rp. 377.044.328 and IRR of 6,16%. The conclusion that can be drawn based on research is that Mr. Khoiri’s dairy farm bussines is feasible to be developed because the NPV value is > 1 (positive). Value Benefit Cost Rasio, Return Cost Rasio, and Internal Rate Return > 1 (positive).